Antimicrobial Efficacy of Mentha spicata Essential Oil and Nisin in Combination on Listeria monocytogenes - MH Moosavy; R Mahmoudi; S Davudi; N Shavisi (Institue of Medicinal Plants, ACECR, 2013)
Background: Natural biopreservative are as alternative approach for controlling growth of foodborne microorganisms such as Listeria monocytogenes. Essential oils (EOs) possess antibacterial properties. Mentha is one of the most common aromatic plants that widely used as medicinal and biopreservative in foods. Nisin a well known antibacterial peptide to effectively antagonize a broad spectrum of bacteria, and is widely used as preservative in foods. Objective: The aim of this work was to investigate of the antimicrobial efficacies of nisin and Mentha spicata essential oil in combination against Listeria monocytogenes. The effects of different temperatures (4, 9 and 14°C), pH (5, 6 and 7) and NaCl concentrations (0, 1, 2 and 4%) were determinate. Methods: Description study. Results: Essential oil content of M. Spicata had 18 components. The dominant active components were carvone (78.76%), limonene (11.50%) and menthol (1%). Minimum inhibitory concentrations for the essential oil and nisin were 160µl/ml and 320IU/ml, respectively. A synergy of low pH values, high temperatures and high NaCl concentrations was observed. Conclusion: Our results found that the combination effects of M. Spicata and nisin in all experimental concentrations significantly reduced the numbers of L. monocytogenes.